A content review of buprenorphine training programs for pharmacists - Scott A. Davis; Robyn Dryer; William Zule; Bayla Ostrach; Delesha M. Carpenter (Elsevier, 2022)
Objectives: To identify and describe continuing education (CE) credit-bearing training programs for pharmacists that cover buprenorphine dispensing. Methods: Five CE databases were searched for trainings that were in English, targeted to pharmacists, addressed use of buprenorphine for opioid use disorder treatment, not state-specific, accredited by the Accreditation Council for Pharmacy Education, and available for online registration. Results: Twelve trainings met the inclusion criteria. The most common topics covered were background and statistical information (10 trainings) and the clinical role of buprenorphine in medication assisted therapy (9 trainings). No training covered all 10 topics assessed. Seven programs included content on prescribing barriers, but of those, only two briefly addressed buprenorphine dispensing barriers, and none addressed the widespread belief that the Drug Enforcement Administration sets limits on the amount of buprenorphine that can be ordered and stocked. A majority of the programs (75%) addressed the clinical details of treatment, but only five addressed social barriers, such as stigma. Conclusion: Future trainings should develop and increase pharmacists' awareness of content to address the gaps identified in this study so they can supplement existing trainings, especially related to DEA and wholesaler regulations and thresholds, communication, stigma, and ways of overcoming these.